DO SUPERCHRONS OCCUR WITHOUT ANY PALAEOMAGNETIC WARNING? - Hulot G.; Gallet Y. (My University, 2003)
The mainly dipolar geomagnetic field generated by the geodynamo within the Earth's liquid core has reversed its polarity many times in the past. This succession of intervals of alternate polarity defines the geomagnetic polarity time scale (GPTS), usually interpreted as resulting from a Gamma renewal process, the rate of which would be controlled by the boundary conditions imposed by the mantle on the core. In this interpretation, boundary conditions would have occasionally evolved towards being unfavourable to reversals, leading the (reversal) rate of the process to progressively decrease and reach zero at least twice, causing the onset of the so-called Kiaman and Cretaceous very long polarity intervals (superchrons). Here we reconsider this causal link. Analysing the latest and best constrained GPTS (thanks to the continuous record provided by marine magnetic anomalies) describing the past 160 Myr, we found that contrary to earlier claims, no long-term behaviour over the ~40 Myr preceding the Cretaceous superchron can be seen in the reversal rate that could explain its onset at ~120 Ma. More generally, it turns out that hardly any special behaviour can be identified in the GPTS, which could have announced this superchron. Only the occurrence of the longest of all pre-superchron intervals (CM1n), ~3 Myr before the onset of the superchron, could be identified as a precursor. Such a behaviour could possibly be the consequence of medium-term (on the 10 Myr time scale) changes in the boundary conditions imposed by the mantle on the core. But we note that the sole analysis of the GPTS does not allow this to be tested. In fact, it appears that a single stationary process could also explain the entire pre-superchron GPTS, with the only possible exception of CM1n. This suggests that the occurrence of superchrons does not necessarily require changes in boundary conditions and could simply attest for a sudden non-linear transition between a reversing and a non-reversing state of the geodynamo.
Keywords: GEOMAGNETIC FIELD; REVERSALS; SUPERCHRONS; STATISTICS; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая